Village Enterprise 4.0: Marketing Communication Innovation Driving Rural Economic Impact - Erwin, Erwin; Burham Isnanto; Ari Amir; Koki Rahmat (Jurnal Multidisiplin Indonesia, 2025)
The digital revolution has transformed Village-Owned Enterprises (BUMDes) marketing and management operations, with this study combining Integrated Marketing Communication Theory and Marketing Mix frameworks to examine digital transformation by developing an integrated model connecting marketing communication strategies, management information systems, digital competencies, and resource management. Employing a cross-sectional quantitative design with 174 participants selected through the Slovin formula and utilizing structured questionnaires analyzed via PLS-SEM methodology, the research reveals significant impacts of marketing communication strategies (β=0.689), management information systems (β=0.667), digital competencies (β=0.614), and resource management (β=0.638) on BUMDes performance. The investigation, conducted in the Bangka Belitung Islands Province, aims to evaluate digital transformation's influence on BUMDes performance and rural economic development, with the research model accounting for 72.7% of BUMDes performance variance and 70.8% of rural economic impact variance, thus establishing a comprehensive framework for BUMDes digital transformation.